"Eine Gesellschaft, die ihre Jugend verliert, ist verloren.": Das hochschulpolitische Konzept der SED am Beispiel der Technischen Hochschule/ Universität Karl-Marx-Stadt und die daraus resultierende Verantwortung der FDJ zwischen 1953 und 1989/90 - Kausch, Jana (Universitätsverlag Chemnitz, 2009)
The universities, colleges and technical schools showed an important part in the social system of the socialism. By considering the creation of the science sector, the meaning, which was ascribed by the SED in the "political conquest of the universities and colleges" became important. Two important duties of the universities of the GDR were: on the one hand, it was a matter to allow students to achieve a sound and qualitatively high education. On the other hand, they should educate the students political-ideologically and the political education stood at the first and the education at the second position. Firstly the work examines, with which provisions (f.e.: The second and third university reform) the GDR government tried to abolish the autonomy of the college and to politicise the educational institution. A second topic is to analyse how these changes have affected the Technical college/university Karl-Marx-Stadt and how the FDJ perceived its education role in the college/ university. Summing up it must be said, that although in the "study [...] almost nothing went without FDJ, but everything with it", the FDJ could not meet its requirements. Even who was persuaded of that world view felt that the approaches and impact often were wooden and authoritarian and not straightened to his needs. The FDJ only understood insufficiently to be a connection between party and youth. The students themselves were less interested in politicisation than in the study and its external-university life, so that they were rather weary of the permanenet ideology.